The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5fd00097a
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule fluorescence resonance energy transfer scanning near-field optical microscopy: potentials and challenges

Abstract: A few years ago, single molecule Fluorescence Resonance Energy Transfer Scanning Near-Field Optical Microscope (FRET SNOM) images were demonstrated using CdSe semiconductor nanocrystal-dye molecules as donor-acceptor pairs. Corresponding experiments reveal the necessity to exploit much more photostable fluorescent centers for such an imaging technique to become a practically used tool. Here we report the results of our experiments attempting to use nitrogen vacancy (NV) color centers in nanodiamond (ND) crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…A Förster distance of 15 nm was found. Sekatskii and co-workers [122] reported on unsuccessful experiments on FRET transfer between a scanning NV and a dye molecule, despite previous demonstration of FRET to dye molecules covalently bonded to NDs [8]. This finding might relate to a varying quantum efficiency (QE) for NV centers in NDs [59], the need for accurate control of the ND surface (graphite layers), as well as to large stand-off distances when attaching an ND to a scanning probe tip.…”
Section: Near-field Microscopy With Nv Centersmentioning
confidence: 76%
See 1 more Smart Citation
“…A Förster distance of 15 nm was found. Sekatskii and co-workers [122] reported on unsuccessful experiments on FRET transfer between a scanning NV and a dye molecule, despite previous demonstration of FRET to dye molecules covalently bonded to NDs [8]. This finding might relate to a varying quantum efficiency (QE) for NV centers in NDs [59], the need for accurate control of the ND surface (graphite layers), as well as to large stand-off distances when attaching an ND to a scanning probe tip.…”
Section: Near-field Microscopy With Nv Centersmentioning
confidence: 76%
“…In recent years, the highly-photostable emission of individual NV centers has triggered several efforts to realize near-field sensing based on NV centers [8,26,122,123]. In general, near-field-based imaging, where a sample is illuminated by the near-field of a light source, allows a higher resolution than far field-based techniques and is able to beat the Abbé limit of resolution.…”
Section: Near-field Microscopy With Nv Centersmentioning
confidence: 99%
“…The performance of the aperture bent SNOM probes has been assessed exploiting them as probes of the slightly modernized customarily made scanning near-field optical microscope, whose main features were discussed earlier [ 4 , 23 ]. In Figure 7(a) , we present the topographical image of 677-AFM calibrating grating, 2000 lines/mm (Ted Pella, Redding, CA, USA) routinely used to calibrate Atomic Force Microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning near-field optical microscopy (SNOM) technique enables overcoming Abbe diffraction limit of far-field optics and obtaining simultaneously optical and topographical images; see, for example, [ 1 3 ] for recent reviews. While the optical resolution of the method is limited by an aperture size and is typically 50–100 nm, an excellent spatial resolution in a topography channel quite comparable with Atomic Force Microscopy and enabling in particular cases even the imaging of individual single strand DNA molecules [ 4 ] can be realized. Naturally, we need a convenient and precise method to control the distance between the tip and sample for the successful operation of any SNOM device.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al achieved sub-10-nm resolution for fluorophores, and observed the helical rise of A-form DNA using an apertureless NSOM [90]. It is obvious that the improvement in the resolution of near-field fluorescence images has been one of the most important research targets in the NSOM field [91]. …”
Section: Optical Properties Of Dna-cnt Hybrids By Near-field Scannmentioning
confidence: 99%